Voter Education and Election Monitoring: The Role of Academics in Realizing Clean and Dignified Elections in Pesawaran Regency - Kartadinata, Andriansyah; Pradana, M. Rafieq Adi (CV. Tripe Konsultan, 2025)
Pilkada is one of the main mechanisms in the local democratic system in the region which aims to elect regional leaders directly by the people. The implementation of regional elections in various regions is still marred by various problems such as money politics, administrative violations and vote manipulation. Low public awareness of the importance of active participation in the election process also worsens the quality of local democracy. In this context, academics as an independent element have a strategic role in providing education to voters and monitoring regional elections in order to realize clean and dignified elections. The service article seeks to identify the role of academics in increasing public political awareness through voter education as well as evaluating the effectiveness of monitoring carried out by academics during the regional elections in Pesawaran Regency. The service methods used include seminar-based education and outreach, direct monitoring in the field, as well as interviews with various related parties, such as regional election organizers and the voting public. The data obtained was then analyzed qualitatively to provide a comprehensive picture of the impact of these activities on improving the quality of regional elections. The results of the service show that the education carried out succeeded in increasing the public's understanding of their rights and obligations in regional elections and reducing the potential for violations, such as money politics and intimidation. Academics involved in monitoring are also able to make real contributions by recording various violations and providing data-based input to Pilkada organizers. Apart from that, the success of this program is also measured by the increasing political awareness of the community and their active participation in monitoring the running of the regional elections. Based on existing findings, it can be concluded that the involvement of academics has a significant impact in increasing the transparency and integrity of regional elections. Therefore, it is recommended that academic involvement in the election process continue to be increased, both through continuous education and building a network of independent observers based on the academic community in various regions. In this way, it is hoped that future regional elections can run more cleanly, honestly and fairly.